The heterogeneous impacts of conditional cash transfers on labor force participation the case of Pantawid Pamilyang Pilipino Program - Amores, Crisandra A.; Mutuc, Lorenz L.
Using the cross-sectional data from the merged 2018 Labor Force Survey (LFS) and Family Income and Expenditures Survey (FIES), we employed a logit regression to determine the effects of the Pantawid Pamilyang Pilipino Program (4Ps) on the labor market outcomes of its adult recipients. The results revealed a positive and significant program impact on the household heads’ labor force participation. This finding is also consistent and robust across the different models tested. A Filipino household head who receives CCT has an 11.7 percent higher probability of participating in the labor force than a household head who does not receive CCT. We also found evidence of the heterogeneity of the effect depending on the household heads' sex, type of residence (urban-rural), and level of per capita income. There is a disincentive for female and rural household heads to participate in the labor market, whereas there is an incentive for nonpoor household heads. Such heterogeneity in the impact of CCT on labor force participation holds essential clues as to what needs to be done by governments, along with promoting investment in human capital and nutrition, to reduce intergenerational cycles of poverty. This includes proper targeting among female household heads and complementary employment opportunities in rural areas. We recommend that future studies focus on households' combined work hours to assess whether there is a transfer of household work into the informal sector from the formal sector. In this approach, new information can be obtained regarding the distribution of labor hours between formal and informal sectors, women and men, and rural and urban areas. This will enable policymakers to identify different and more nuanced types of potential program dependence, which may warrant a reevaluation of the methods used to target the poor in social programs.